Hyperglycemia Aggravates Hepatic Ischemia and Reperfusion Injury by Inhibiting Liver-Resident Macrophage M2 Polarization via C/EBP Homologous Protein-Mediated Endoplasmic Reticulum Stress - Rao, Zhuqing; Sun, Jie; Pan, Xiongxiong; Chen, Ziyang; Sun, Heliang; Zhang, Panpan; Gao, Mei; Ding, Zhengnian; Liu, Cunming (Frontiers in Immunology, 2017)
Aggravated liver ischemia and reperfusion (IR) injury has been observed in hyperglycemic hosts, but its underlying mechanism remains undefined. Liver resident macrophages (Kupffer cells, KCs) and endoplasmic reticulum (ER) stress play crucial roles in the pathogenesis of liver IR injury. In this study, we evaluated the role of ER stress in regulating KC activation and liver IR injury in a streptozotocin-induced hyperglycemic/diabetic mouse model. Compared to the control group, hyperglycemic mice exhibited a significant increase in liver injury and intrahepatic inflammation following IR. KCs obtained from hyperglycemic mice secreted higher levels of the pro-inflammatory factors TNF-α and IL-6, while they secreted significantly lower levels of the anti-inflammatory factor IL-10. Furthermore, enhanced ER stress was revealed by increased C/EBP-Homologous Protein (CHOP) activation in both IR-stressed livers and KCs from hyperglycemic mice. Specific CHOP knockdown in KCs by siRNA resulted in a slight decrease in TNF-α and IL-6 secretion but dramatically enhanced anti-inflammatory IL-10 secretion in the hyperglycemic group, while no significant changes in cytokine production were observed in the control group. We also analyzed the role of hyperglycemia in macrophage M1/M2 polarization. Interestingly, we found that hyperglycemia inhibited IL-10-secreting M2-like macrophage polarization, as revealed by decreased Arg1 and Mrc1 gene induction accompanied by a decrease in STAT3 and STAT6 signaling pathway activation. CHOP knockdown restored Arg1 and Mrc1 gene induction, STAT3 and STAT6 activation, and most importantly, IL-10 secretion in hyperglycemic KCs. Finally, in vivo CHOP knockdown in KCs enhanced intrahepatic anti-inflammatory IL-10 gene induction and protected the liver against IR injury in hyperglycemic mice but had no significant effects in control mice. Our results demonstrate that hyperglycemia induces hyper-inflammatory activation of KCs during liver IR injury. Thus, hyperglycemia-induced CHOP over-activation inhibits IL-10-secreting M2-like macrophage polarization by liver resident macrophages, leading to excessive inflammation and the exacerbation of liver IR injury in diabetic/hyperglycemic hosts. This study provides novel mechanistic insight into macrophage inflammatory activation under hyperglycemic conditions during liver IR.